Stunting: Penyebab, Gejala, dan Pencegahan - Fauziah, Jihan; Trisnawati, Khansa Dinah; Rini, Khansa Pramesti Sulistyo; Putri, Suci Utami (Indonesian Journal Publisher, 2024)
Currently, the Indonesian government has a target of reducing stunting rates. Stunting is a condition where there is malnutrition in children where children around the world suffer from stunting. This research uses a literature review with data collection sources coming from scientific articles, theses, books, theses. Stunting occurs due to many factors, namely maternal education, economy, immunization, breastfeeding, and infectious diseases. Stunting can be prevented by breastfeeding, immunization, diet, and health checks.